Solvent-induced viscosity changes in ionic liquids - a review - Khupse, Nageshwar D.; Kumar, Anil (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2010)
The high viscosity of several ionic liquids is an undesirable property for their applications in a variety of chemical reactions and electrochemical devices. Addition of a solvent in an ionic liquid is known to reduce its high viscosity to a great extent. In this review, an attempt has been made to examine the published data on the reduction in viscosities of many ionic liquids upon the addition of molecular solvents, including water. A tentative description has been provided for the drop in viscosities under these conditions. Analysis of the viscosity data with the help of empirical equations has been summarized. This critical review also outlines the future outlook of the required studies that might be useful to those who are interested in using ionic liquids for a variety of applications.
Keywords: ionic liquids; solvent; viscosity